Teledermatology: Case selection and consultation “Technology is best when it brings patient–Physician together.” - Garehatty Rudrappa Kanthraj (Clinical Dermatology Review, 2023)
Teledermatology consultation (TC) is an effective, safe, and fast medium to reach one who is difficult to reach. The scope of TC is triage, diagnosis, counseling, and follow-up care. Feasibility studies for diagnosis and follow-up care by TC are analyzed. Teledermatology has been extensively evaluated in terms of diagnostic accuracy with respect to teledermatology tools, clinical outcomes, patient and provider satisfaction, and costs. Follow-up care by TC in cutaneous, esthetic surgeries and lasers is documented and widely used. We review and analyze the commonalities and differences between diagnosis and follow-up care using TC. There is a need to define case selection for TC. A dermatologist has to select an appropriate case and define the purpose for TC. A case with characteristic morphology and distribution of diagnosis is performed by TC. Follow-up care is provided by TC for cases with longer duration with remission and exacerbation. Interpretation of multiple patch test readings is performed by TC. Initial in-person examination is followed by TC to provide follow-up care. Various clinical situations and technical factors TC should not be offered are analyzed. A dermatologist should be aware of these clinical situations and technical factors and offer TC. Store-and-forward teledermatology and mobile messenger apps (e.g., WhatsApp) are commonly used to perform capture, transfer, and store clinical images. A dermatologist should realize providing follow-up care is one of the most important scopes of TC. Patient and physician satisfaction is best achieved for follow-up care. Further studies are needed in this area.